A Study of English Language Teaching in India: Enhancing English Language Teaching through Cultural Relevance and the Visual Arts (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In learners of English as a second language are students classified as “limited English proficient” (LEP) because they come from a home where a language other than English is spoken and score at below “Proficiency” on the LAB-R or score at the Beginning, Intermediate, or Advanced level of English as measured by the NYSESLAT. Diverse student profiles exist within the overall classification of LEP. There are LEPELLs who may be gifted and there are many with a high level of proficiency in their native language. Others may not be able to read or write in their native language because they have had a limited or interrupted formal education in their own country. Finally, there is a population of LEP students who have been identified as having special needs and have been referred for special education services. For ELLLEP students, it is imperative to make teaching and learning culturally relevant and to enable access to prior knowledge upon which new skills and concepts can be built. It is critical for educators to understand the ways in which students’ cultural and linguistic backgrounds profoundly influence their experiences in the classroom. The visual arts enhance language development by offering non-verbal methods for communication and understanding and by providing a platform for students to create mental images. Integrating the arts into language arts and the content areas for ELLs can give students the opportunity to engage in new and varied approaches while gaining positive emotional responses to learning, understanding others and communicating their own ideas.